Unravelling the disease associated metabolites in mutant lines of spanish jasmine (Jasminum grandiflorum) - Srinidhi , M V; Ganga , M; Thamaraiselvi , S P; Geethanjali , S; Muthulakshmi , P (Plant Science Today, 2025)
Jasminum grandiflorum cv. Pink pitchi is a novel type in Spanish jasmine which differs from the common cultivars owing to its flower buds which has pink bottom and pure white colour on its upper side. Mutations were made to create variations in plant type and flower bud through physical and chemical mutagens which was done three years ago. Those plants were examined for the current study and among the mutant population, two promising mutants, PP-LBR-2 and PP-LBR-3 were selected based on their yield performance. Of these two mutant lines, PP-LBR-2 was found to be free of Alternaria leaf blight (Alternaria alternata) symptoms, while PP-LBR-3 expressed blight symptoms under field conditions. Leaf samples were collected from these two mutant lines and subjected to Gas chromatography-mass spectrometry (GC-MS) analysis for identifying the metabolites present in the samples, which correlate with the disease. The metabolite profiling resulted in identification of various compounds as shown in heat map. PP-LBR-3 contained metabolites that induced susceptibility and pathogen invasion, PP-LBR-2 accumulated chemicals associated with antimicrobial and defensive properties. Interestingly, n-hexadecanoic acid, squalene, phytol and tetradecanoic acid were among the shared molecules with pharmacological activity verified in the previous literature that were found in both lines. The research highlights how varying responses to illness in pink pitchi jasmine are brought about by metabolic heterogeneity caused by mutations. These findings stress the therapeutic value of new mutant lines and provide valuable information for breeding disease-resistant jasmine.